2011
DOI: 10.4103/0970-4388.86369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mesiodens among six- to seventeen-year-old school going children of Indore

Abstract: The present study gives an insight into the prevalence of mesiodens among school going children of Indore city. A coincidental finding in our study has been the high risk of trauma associated with the occurence of mesiodens. This finding makes it mandatory to include mesiodens as a risk factor in traumatic dental injuries. Early diagnosis and management of these otherwise considered mild factors must be made mandatory in pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 0 publications
3
28
0
12
Order By: Relevance
“…14 Ambas denticiones se ven afectadas, pero en la segunda dentición su prevalencia es superior que en la primaria. 15 Muchos estudios muestran que la presencia de mesiodens afecta a los hombres más que a las mujeres, en una relación 2:1.…”
Section: Discussionunclassified
“…14 Ambas denticiones se ven afectadas, pero en la segunda dentición su prevalencia es superior que en la primaria. 15 Muchos estudios muestran que la presencia de mesiodens afecta a los hombres más que a las mujeres, en una relación 2:1.…”
Section: Discussionunclassified
“…11 Most of the mesiodens in our study were erupted in 54.7% cases similar to study by Sulabha et al 12 and impacted mesiodens were 45.3% which was lower than other studies in literature. 8,11,13 This may be explained by presence of large numbers of conical mesiodens which are more likely to erupt.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the present crosssectional retrospective study based on the hospital records, 40 patients showed the presence of 53 mesiodens. The male female ratio in present study was 3:1 which was similar to findings of other studies like, Kim et al, 9 Asaumi et al 7 and Huang et al 4 that reported 4:1, 2.8:1 and 2.5:1, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hovewer, there can be confusion about when mesiodens should be surgically removed, or whether they should be retained and followed up instead of being treated via multidisiplinary aprroaches (15,28,30). Removal of mesiodens is indicated in the following situations; inhibition or delay of eruption, displacement of the adjacent tooth, interference with orthodontic appliances, presence of a pathological condition, or spontaneous eruption of the supernumerary tooth (25,(31)(32).…”
Section: Discussionmentioning
confidence: 99%